TRANSITIONAL STAGES OF A BUSINESS FAILURE. - Fitzpatrick, Paul J. (The Accounting Review, 1934)
There are, indeed, several transitional periods of a business failure, for a failure usually does not occur as quickly and unexpectedly as an accident may, but has generally passed through several stages. A failing business enterprise may be likened to that of an individual suffering from a minor illness which, if not properly remedied, may develop into a serious disease, perhaps death itself. The first stage, for a want of a better name, may be called, in a pathological sense, the period of incubation. At this point one or more unfavorable conditions are quietly or insidiously developing. The owner of the business may not be aware of them, just as an individual is often unaware of the presence of a certain disease slowly developing in his constitution. These deep seated, slow-acting causes may not be recognized now, but later on they will become apparent. The second step is the financially embarrassed stage. During the life of any normal business enterprise there may be one or more times when a firm urgently needs cash to meet its maturing obligations. The third stage, termed financial insolvency occurs when a concern is unable to procure much-needed funds to meet its maturing or pressing obligations. The fourth stage, known as total insolvency occurs when liabilities exceed physical assets.